Reingeniería Del Talento Humano Y Desempeño Laboral En La Empresa Suministros Del Pacifico De La Ciudad De Guayaquil. - AGUAS PUTÁN, ROBERTO (2014)
This thesis is based on a reengineering of human talent and job performance in the Company Supplies Pacific city of Guayaquil, it will contain procedures to ensure a reasonably timely and necessary changes in policy work activities, to be more efficient performance of workers in the area of production, and achieve growth in production volume increases economic performance also make the company competitive in the domestic market. The purpose of reengineering to apply with respect to human talent and performance in the production area will develop mechanisms leading to designate tasks and functions competency, ir distributed work activities each worker according to knowledge, skills and knowledge. An analysis of performance evaluation of the performance of the work it performs in the production area is implemented, we are confident that the company Supply Pacific will implement the proposed through a reengineering of human talent changes, to improve job performance and optimize operational, administrative and financial results for the business. It is necessary and important that the company keeps Pacific Supply in the National competitive market for product quality cardboard boxes used to pack and pack fruits especially bananas, to foreign markets, stable production in the shortest time possible and even low-cost, factors affecting to be within the competitive market.